Selecting The Best Supplier in Procurement Section (Goods Spot Purchase) - Departement SCM With Analytical Hierarchy Process (AHP) Method - Marline Louister Siregar; Suparno Suparno (IPTEK Journal of Proceedings Series, 2020)
Choosing suppliers is one of the upstream supply chain areas that affect the quality of the products produced by a company. This study aims to develop a framework for selecting the best suppliers/suppliers in the Procurement Section (Goods Spot Purchase), the SCM Department at the company. According to the AHP method, this study will determine the main criteria through interviews, questionnaires, and pair-wise comparison in developing AHP, and determine the sub-criteria based on the main criteria. The result is forming the best supplier selection framework based on the requirements set by the company. Also, the main criteria for selecting the best suppliers are price, quality, delivery. flexibility and response, and Vendor Performance. This study might be beneficial to be implemented in the company, in terms of the best supplier selection in the Non-stock purchase section of the Procurement Section, the SCM Department objectively.